A facile morphology tunable strategy of Zn-MOF derived hierarchically carbon materials with enhanced supercapacitive performance through the solvent effect. Issue 47 (18th November 2022) - Miao, Rui; Sun, Chaohua; Li, Jipeng; Sun, Yanzhi; Chen, Yongmei; Pan, Junqing; Tang, Yang; Wan, Pingyu
Abstract : Metal–organic framework (MOF) derived porous carbon materials have been widely applied as active materials for supercapacitors due to their large specific surface area and ordered pore structure. Abstract : Metal–organic framework (MOF) derived porous carbon materials have been widely applied as active materials for supercapacitors due to their large specific surface area and ordered pore structure. This paper presents a facile and effective strategy to regulate the morphology of a zinc-based metal–organic framework (Zn-trimesic acid, Zn-BTC) by adjusting the ethanol content in a solvent, which can effectively change the pore structure of Zn-BTC derived porous carbon (PC). The optimal PC prepared in 50% ethanol displays a rodlike structure with a large specific surface area (SSA) of 1930 m 2 g −1 and an average pore size of 2.9 nm. This material shows an excellent rate performance with 78.8% capacitance retention when the current density increases from 1 A g −1 to 100 A g −1 and outstanding electrochemical stability with only 2.2% decline of capacitance after 200 000 cycles at 50 A g −1 . Moreover, the assembled symmetrical capacitor shows a high energy density of 16.09 W h kg −1 at 698 W kg −1 and 11.89 W h kg −1 at a high power density of 41.56 kW kg −1 . This method would provide a new pathway for the preparation of carbon materials with an adjustable pore size for high-performance supercapacitors.